DNA‐Directed Assembly of a Cell‐Responsive Biohybrid Interface for Cargo Release. Issue 7 (24th May 2021) - Sun, Pengchao; Scharnweber, Tim; Wadhwani, Parvesh; Rabe, Kersten S.; Niemeyer, Christof M.
Abstract: The development of a DNA‐based cell‐responsive biohybrid interface that can be used for spatially confined release of molecular cargo is reported. To this end, tailored DNA–protein conjugates are designed as gatekeepers that can be specifically cleaved by matrix metalloproteases (MMPs), which are secreted by many cancer cells. These gatekeepers can be installed by DNA hybridization on the surface of mesoporous silica nanoparticles (MSNs). The MSNs display another orthogonal DNA oligonucleotide that can be exploited for site‐selective immobilization on solid glass surfaces to yield micropatterned substrates for cell adhesion. Using the human fibrosarcoma cell line HT1080 that secretes MMPs, it is demonstrated that the biohybrid surface is specifically modified by the cells to release both MSN‐bound gatekeeper proteins and the encapsulated cargo peptide KLA. In view of the enormously high modularity of the system presented here, this approach promising for applications in drug delivery, tissue engineering, or other areas of nanobiotechnology is considered. Abstract : Tailored DNA–protein conjugates (green) are designed as gatekeepers for mesoporous silica nanoparticles (MSNs, magenta). DNA‐directed self‐assembly of the gatekeeper, MSNs, and micropatterned surfaces leads to formation of a biohybrid interface which can be selectively switched by cells that secrete matrix metalloproteases to release proteins and molecular cargo from the MSN containers.